Ergogenic effect of mengkudu (Morinda citrifolia L.) leaf extract on obese sprague dawley rats using metabolomic approach - Abdul Majid, Nordiana (2019)
Natural products are getting much acceptance as ergogenic aids, in enhancing physical performance, not only among the athletes but also the general population. Obese person mostly has reduced desire and ability to exercise; resulting in difficulty to reduce weight and fat in the body. Thus, they need to boost their energy production so that they can be more active and healthier. In this study, Morinda citrifolia leaf extract (MLE) believed to possess ergogenic property was used to evaluate its effect on an obese animal model by using Forced Swimming Test (FST) as endurance exercise and the changes in metabolic profiles of exercise obese rats after treatment was also identified using 1H-NMR based metabolomics. The rats were fed with high fat diet (HFD) for 12 weeks for obese development. Once become obese, all the rats undergone endurance exercise every two weeks for 8 weeks together with treatment. Three different dosages of MLE used were 50 mg/kg, 100 mg/kg and 200 mg/kg of body weight (BW) together with two positive Control, 5 mg/kg caffeine and 100 mg/kg green tea. Blood and urine were collected for the metabolomic study. Animal study carried out showed that rats fed 200 mg/kg BW MLE demonstrated the longest endurance capacity of approximately three times as long as that of green tea and caffeine. The rats were also found to have lower lactate level, suggesting that energy metabolism was more effective in these rats. In addition, lactate dehydrogenase enzyme (LDH) activity, muscle injury indicator, was found to be lowest in rats fed the highest MLE level. Interestingly, the same effect was not seen in rats fed either caffeine or green tea, indicating that MLE treatment able to protect rat’s muscle. In metabolomic, multivariate analysis including unsupervised and supervised analysis were used to identify the potential biomarkers. The study showed that feeding the rats at a dose of 200 mg/kg BW MLE altered metabolites present in the serum of exercised obese rat. The PLS-DA score plots showed distinct separation between normal rats with that of green tea and caffeine treatments, and instead, were very similar to that of 200 mg/kg BW MLE suggesting that the 200 MLE feeding was more effective in improving endurance capacity in comparison to that of either synthetic or natural ergogenic substances. Metabolites such as glutamine, glycerol, glycine, acetoacetate, taurine, carnitine, succinate, pyruvate and 2-hydroxybutyrate were found to be higher after MLE treatment suggested that changes in metabolic pathways which included carbohydrate, lipid and energy metabolism. In conclusion, this study reports on the potential ergogenic property of high dose of MLE based on the enhancement swimming capacity, energy metabolism and metabolic perturbation in the exercised obese rats.